2021
DOI: 10.1007/s00436-021-07099-7
|View full text |Cite
|
Sign up to set email alerts
|

Mastomys natalensis (Smith, 1834) as a natural host for Schistosoma haematobium (Bilharz, 1852) Weinland, 1858 x Schistosoma bovis Sonsino, 1876 introgressive hybrids

Abstract: Cercarial emission of schistosomes is a determinant in the transmission to the definitive host and constitutes a good marker to identify which definitive host is responsible for transmission, mainly in introgressive hybridization situations. Our goal was to test the hypothesis that micro-mammals play a role in Schistosoma haematobium, S. bovis, and/or S. haematobium x S. bovis transmission. Small mammal sampling was conducted in seven semi-lacustrine villages of southern Benin. Among the 62 animals trapped, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…Our findings showed polymorphism of the egg morphotype, with 32.2% of the schistosome eggs comprising the atypical spindle-shaped group. Previous studies have reported the presence of two or three morphotypes of schistosome eggs recovered from both infected humans and animals [21,22,23]. The presence of the different morphotypes in the schistosome eggs recovered from human urine samples in Ogun State suggests hybridization among the Schistosoma groups in the area.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings showed polymorphism of the egg morphotype, with 32.2% of the schistosome eggs comprising the atypical spindle-shaped group. Previous studies have reported the presence of two or three morphotypes of schistosome eggs recovered from both infected humans and animals [21,22,23]. The presence of the different morphotypes in the schistosome eggs recovered from human urine samples in Ogun State suggests hybridization among the Schistosoma groups in the area.…”
Section: Discussionmentioning
confidence: 93%
“…The zoonotic potential of the hybrids would strongly impact the parasite transmission in the field, in and out of endemic areas, and may hamper our capacity to maintain adequate control strategies as schistosomiasis treatment focuses almost exclusively on humans. Recent studies are now showing the presence of not only S. bovis, S. haematobium, and S. mansoni in rodents (hosts in which hybridization may occur), but also the occurrence of S. haematobium x bovis hybrids in such hosts in Senegal [33,34] and Benin [35] although the importance of rodents in transmission dynamics needs further exploration. Moreover, beside widespread investigation of animal reservoir in Senegal [26] to date only one study in Benin suggests that other animals such as cattle may be natural hosts for such hybrid parasites [27].…”
Section: Implications For Host Spectrum and Parasite Distributionmentioning
confidence: 99%
“…Young Northern Senegalese visit France since decades for occupational opportunities in the gastronomic sector, e.g., the restaurant Sainte-Lucie de Porto Vecchio about 15 km from the bathing sites of the Cavu River, which does not constitute formal proof, but helps to better understand the likely parasitic spread. However, data available do not explain parasitic survival during less favorable winter months, and recurrence in subsequent years beyond 2014; a potential zoonotic role of livestock and/or rodents, the latter being capable of serving as hosts for Sb and ShxSb crossbreeds, but not Sh, as seen in the SRB and recent Beninese investigations is suspected [ 54 , 81 , 90 , 94 , 95 , 96 , 97 ]. Interestingly, Savassi and colleagues did confirm the presence of ShxSb hybrids in cattle and rodents ( Mastomys natalensis ) in addition to schoolchildren in Kessounou, Benin [ 97 , 98 ] in contrast to research performed in Senegal [ 45 ] and Cameroon [ 99 ].…”
Section: Schistosome Hybrids Across Africa—the Tip Of the Icebergmentioning
confidence: 99%
“…However, data available do not explain parasitic survival during less favorable winter months, and recurrence in subsequent years beyond 2014; a potential zoonotic role of livestock and/or rodents, the latter being capable of serving as hosts for Sb and ShxSb crossbreeds, but not Sh, as seen in the SRB and recent Beninese investigations is suspected [ 54 , 81 , 90 , 94 , 95 , 96 , 97 ]. Interestingly, Savassi and colleagues did confirm the presence of ShxSb hybrids in cattle and rodents ( Mastomys natalensis ) in addition to schoolchildren in Kessounou, Benin [ 97 , 98 ] in contrast to research performed in Senegal [ 45 ] and Cameroon [ 99 ]. The possibility of zoonotic parasite transmission to human hosts would derange dramatically well-established prevention and control measures for schistosomiasis.…”
Section: Schistosome Hybrids Across Africa—the Tip Of the Icebergmentioning
confidence: 99%